Medical education scholarship: An introductory guide: AMEE Guide No. 89. (August 2014) - Crites, Gerald E.; Gaines, Julie K.; Cottrell, Scott; Kalishman, Summers; Gusic, Maryellen; Mavis, Brian; Durning, Steven J.
Abstract: This AMEE Guide provides an overview of medical education scholarship for early career scholars, based upon a summary of the existing literature and pragmatic advice derived from the experience of its authors. After providing an introduction to the principles of scholarship and describing questions that the Guide addresses, the authors offer a conceptual description of the complementary traditions of teaching and educational discovery, and advocate for the development of educational scholars with both traditions. They then describe the attributes of effective mentor–mentee relationships and how early career scholars can identify potential mentors who can fulfill this role. In the subsequent sections, they describe the appropriate development of scholarly questions and other components of a complete scholarly plan, including how to use conceptual frameworks in guiding such plans. From here, they describe methods that align with both the teaching and discovery traditions and provide concrete examples of each. They then provide guidelines for assessing the impact of scholarship, identify the various opportunities for sharing it, and how to effectively interpret and describe it. Additionally, they provide practical advice on how appropriately to demonstrate the scholarship in a promotional packet, including the principle of reflectivity in scholarship. Finally, they address the principles of applied research ethics for educational scholarship and when to consider soliciting approval for scholarly activities by a human research board.